Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii - Magalhães, Wagner F.; Bailey-Brock, Julie; Watling, Les (Zootaxa, 2018)
Several collections of magelonids from Easter Island, Guam in the Mariana Islands and Hawaii were examined. Five magelonids are fully described and illustrated: Magelona anuheone sp. nov. (Easter Island), M. cf. symmetrica Mortimer & Mackie, 2006 (Guam), M. alexandrae sp. nov. (Hawaii), M. cinthyae sp. nov. (Hawaii) and M. paulolanai sp. nov. (Hawaii and Guam). Magelona anuheone sp. nov. has a distinctly longer than wide prostomium with inflated and well-developed prostomial horns, similar to M. montera from the Indian Ocean. Magelona alexandrae sp. nov. belongs to Magelona species with crenulated upper margin of thoracic postchaetal lamellae and also well-developed prostomial horns. Magelona cinthyae sp. nov. is unique among its congeners in that several collected adult individuals presented two or more eyespots in the prostomium, a feature only previously recorded to pelagic larval stages. Magelona paulolanai sp. nov. belongs to a group of species with rudimentary prostomial horns, simple capillaries on chaetiger 9 and tridentate abdominal hooks. All species are illustrated and compared to their morphologically similar congeners.